(3QSGdI aj JaSjQ ShQI Gdedcs - (3fUQ GdghQjfj , fUQ Hf fUQ jhfS GdhaGFj GdghQjfj GdCMeOj, CHh GdhaGA,J (B1291 (3g` s
(3ChdgG (B:s
(3bhdg JYGdi JHGQc(B: (3bGd GHf YHGS QVi Gddg YfgeG hJYGXe Yf UaI GdeNdhbjf s
(3BNQgG (B:s
(3Je GdShQI hGdMeO ddg hGdUdGI hGdSdGe Ydi SjO GdCfGe GdMhJ GdPi Ydjg GdCQV GSeg GdjgehJ HaJM GdJMjI Sjchf GdjgG heG GTJgQ Gfg HGdjGA s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B29 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B93s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs